Creative after effects 7 : workflow techniques for animation, visual effects and motion graphics. - Taylor, Angie, ....- (Amsterdam : Focal, 2006)
Realize your creative potential with a working knowledge of After Effects 7. Renowned artist and designer Angie Taylor demonstrates professional workflows and inspires with practical tutorial lessons that help put the theory (and you!) to work. You'll learn from a comprehensive survey of the new interface and features, with illustrated techniques for animation, visual effects and motion graphics. Practice exercises to reinforce essential techniques, and continuous projects challenge you with fantastically creative uses of the application. The companion DVD includes everything you'll need to complete the tutorials as well as an array of bonus plug-ins and demo software.??A comprehensive survey of the new After Effects 7 interface and toolset??Illustrated techniques for animation, visual effects and motion graphics??Practical tutorial lessons that demonstrate professional workflows??A companion DVD with tutorial media and valuable plug-ins.
Keywords: Computer graphics